Assessing peer influence and susceptibility to peer influence using individual and dyadic moderators in a social network context: The case of adolescent alcohol misuse. (May 2022) - DeLay, Dawn; Burk, William J.; Laursen, Brett
Higher accepted friends are known to influence the alcohol misuse of lower accepted friends, but not the reverse. The present study was designed to address the origins of this influence: Are higher accepted friends particularly influential or are lower accepted friends particularly susceptible to influence? To address this question, we introduce an innovative application of longitudinal social network techniques (RSIENA) designed to distinguish being influential from being susceptible to influence. The results revealed that influence was a product of heightened susceptibility among low accepted adolescents, rather than heightened influence among high accepted adolescents. The findings are consistent with claims that low accepted youth fear the consequences of nonconformity and adjust their behavior to more closely resemble their affiliates.